Existência de padrões com difusibilidade variável e condição de fronteira de Neumann não linear - Sônego, Maicon (Universidade Federal de São Carlos, 2009)
In this work we study a reaction-difusion problem with nonlinear Neumann boundary condition. The objective is to present suficient conditions on the diffusion coeficient so that the problem has an stable nonconstant equilibrium solution. The main tools are some basic results of real analysis, techniques of variational calculus and properties of dynamical systems.
Keywords: Equações diferenciais parciais; Equações diferenciais parciais não-lineares; Equações de reação de difusão (Matemática); Estabilidade linearizada; Equilíbrios estáveis não-constantes; CIENCIAS EXATAS E DA TERRA::MATEMATICA